2019
DOI: 10.3390/ani9121033
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Vasopressin as a Potential Non–Invasive Biomarker of Anxiety in Dogs Diagnosed with Separation–Related Problems

Abstract: Physiological biomarkers of canine anxiety have not been extensively investigated to date. To identify new biomarkers in dogs, we compared behaviorally normal dogs (Control group, N = 13) to dogs diagnosed with separation problems (Case group, N = 13) as they were introduced into a novel environment in the presence of two strangers and subjected to a short episode of separation and reunion with the owner. During the separation phase, dogs in the Case group explored significantly less than controls and were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…In the latest study of salivary AVP in dogs, dogs diagnosed with separation-related problems showed higher salivary AVP levels than a control group when separated from their owner. This result supports further exploration of the use of salivary AVP as an early, non-invasive biomarker of canine anxiety-related disorders [ 30 ].…”
Section: Introductionsupporting
confidence: 79%
“…In the latest study of salivary AVP in dogs, dogs diagnosed with separation-related problems showed higher salivary AVP levels than a control group when separated from their owner. This result supports further exploration of the use of salivary AVP as an early, non-invasive biomarker of canine anxiety-related disorders [ 30 ].…”
Section: Introductionsupporting
confidence: 79%
“…In dogs, vasopressin increase has been associated with acute stress responses (Hydbring-Sandberg et al, 2004) and was also reported in dogs with separation anxiety (Pirrone et al, 2019). Further, lower free, but higher total plasma AVP has been found in aggressive dogs (MacLean et al, 2017b).…”
Section: Vasopressinmentioning
confidence: 76%
“…Therefore, biomarkers play an important role and serve as a proxy when assessing emotion and positive well-being in animals (e.g., von Borell et al, 2007 ; Schmied et al, 2008 , 2010 ; Reefmann et al, 2009a , b ; Coulon et al, 2013 , 2015 ; Briefer et al, 2015 ; Kowalik et al, 2017 ). Heart rate (HR) ( Csoltova et al, 2017 ), heart rate variability (HRV) ( Bergamasco et al, 2010 ; Katayama et al, 2016 ; Travain et al, 2016 ), surface temperature ( Travain et al, 2015 , 2016 ; Csoltova et al, 2017 ), oxytocin ( Odendaal and Meintjes, 2003 ; Mitsui et al, 2011 ; Rehn et al, 2014 ; Nagasawa et al, 2015 ), vasopressin ( Hydbring-Sandberg et al, 2004 ; MacLean et al, 2017a , b , 2018 ; Pirrone et al, 2019 ), cortisol ( Hennessy et al, 1998 , 2006 ; Coppola et al, 2006 ; Bergamasco et al, 2010 ; Shiverdecker et al, 2013 ), and alpha-amylase ( Contreras-Aguilar et al, 2017 ; Hong et al, 2019 ) have been implemented and showed potential usefulness in indirect and noninvasive assessment of positive-emotion in dogs.…”
Section: Positive-emotion Assessment In Dogsmentioning
confidence: 99%
“…In the current study, the video data were coded and analyzed with all study investigators and statistician remaining blind, providing further confidence in the results. Future studies could also involve the use of biomarkers, such as salivary vasopressin, to evaluate efficacy, provided additional work has been done to support their use ( 33 ).…”
Section: Discussionmentioning
confidence: 99%